Referrals to neurologists for headaches not due to structural disease. Issue 12 (December 1981) - Fitzpatrick, R; Hopkins, A
Abstract : Patients attending neurological clinics with headaches that proved not to be due to clearly defined structural disease were interviewed before and after the consultation and approximately one year later. Their expectations of the consultation were ill-formed. About two-thirds of the patients had fears about organic disease although few had psychiatric morbidity. These fears were generally dispelled by the consultation. About one-third of the patients were dissatisfied by the consultation, nearly all by what the neurologist said rather than by what technical procedures he did or did not undertake. Women with a long history of migraine, with significant psychiatric morbidity, and who had initiated the referral themselves were particularly likely to be dissatisfied. Although most patients were still having headaches one year later, visits to the general practitioner for this symptom had greatly declined.